Temperature analysis of the Gaussian distribution modeling the barrier height inhomogeneity in the Tungsten/4H-SiC Schottky diode - Toumi, S.; Ouennoughi, Z.; Weiß, Roland (Applied Physics A: Materials Science and Processing, 2021)
The temperature dependence of the electrical properties of the Schottky barrier contact W/4H-SiC is studied in term of the Werner’s model assuming a Gaussian distribution of the barrier height to model the inhomogeneity of the Schottky interface. The Gaussian distribution is characterized by the parameters ϕ¯ B as a mean barrier height, ρ2, ρ3 as coefficients quantifying the barrier deformation and σs as a standard deviation. The effect of the series resistance Rs and its relation with the standard deviation σs is also reported. A vertical optimization process is used to extract simultaneously all the parameters cited above as function of temperature from the forward current–voltage (I-V) characteristics at temperatures ranging from 303 to 448 K. The temperature dependence of the characterized parameters of the W/4H-SiC Schottky structure enables us to quantify the inhomogeneity state of the Schottky barrier height prevailing at the MS interface in terms of those extracted parameters.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Barrier’s height parameters ϕ¯; Metal–Semiconductor interface inhomogeneity; T; Vertical optimization method; W/4H-SiC